STEP BUDDY: A SCHEME TO ENHANCE THE DANCE SKILLS OF THE SHS STUDENTS - Edrada, Ivy (IJBLE Scientific Publications Community Inc., 2022)
This study analyzed the effectiveness of Step Buddy in improving the basic skills in a dance of Senior High School students. This study addresses the competency code PEH11FH-IIo-t-17, which is to organize sports events for a target health issue or concern. This study used an experimental method and underwent four steps. First, the researcher assessed the learner’s 1st quarter performance and determined the learners who need assistance and those who have potential in dancing. Second, the top ten highest performance grades for the 1st quarter were considered as peer tutors by the researcher. Then, the tutors and tutees met during their vacant time and the researcher monitored the tutoring session. After the said tutorial, the researcher compared the grades of the tutees in the 1st quarter and 2nd quarter to whether there is an increase in their level of performance. The mean score of the 1st and 2nd quarter performance task grades are both analyzed in this research. Overall, the use of Step Buddy can be used effectively to enhance students' ability to enhance skills in dancing. Therefore, there was a significant difference between the 1st and 2nd quarter performance task grades of the students.